Designing a Model to Promote Happiness in High School Students - Sedigheh Sheikh Siyah Banoeieh; Mehdi Bagheri; Parivash Jafari; Naderqoli Qorchian (Iranian Evolutionary Educational Psychology Journal, 2022)
The main purpose of this study was to identify the pattern of promoting happiness in high school students. The method of study was qualitative research via Grounded theory. This grounded theory study explored the pattern of promoting happiness in high school students. Based on it, the semi-structured interviews were conducted with 14 experts and specialists who were selected by theoretical sampling method. To ensure the validity of the research, we used the members checking (interviewees) and triangulation (faculty members) and to calculate the reliability of the coding method, the methods of inter-subject agreement (agreement between two coders) and Kendall agreement formula were used that coefficient of 0.78 was obtained, which is in the favorite range. In order to analyze the data obtained from the interview, thematic analysis method was used. After reaching theoretical saturation, the dimensions and components of happiness promotion in schools were extracted and the pattern of happiness promotion in high school students was identified. Findings revealed that the model of promoting happiness in high school students include two dimensions, internal and external. In the internal dimension, the main categories of the model include: characteristics of students, characteristics of teachers, characteristics of principals, teaching methods, communication and interactions, activities, actions and educational programs of the school, organizational factors and physical space and equipment. In the internal dimension, the main categories include family factors and social factors.